Exploitation in payments to research subjects. - Phillips, Trisha (Bioethics, 2011)
Offering cash payments to research subjects is a common recruiting method but there is significant debate about whether and in what amount such payments are appropriate. This paper is concerned with exploitation and whether there should be a lower limit on the amount researchers can pay their subjects. When subjects participate in research as a way to make money, fairness requires that researchers pay them a fair wage. This call for the establishment of a lower limit meets resistance in two places: (1) denial that the payments offered by researchers are wages for participation; and (2) concern about undue inducement. This paper critically examines these arguments for and against a lower limit. It shows that the need for a lower limit cannot be avoided by adopting a non-wage payment model and that concerns about undue inducement are unjustified in all trials except those that present greater than minimal risk. This analysis suggests the following compromise position: there should be an unconditional lower limit on payment amounts so that researchers cannot offer less than a fair wage, and when researchers cannot satisfy this limit because fairness requires a problematically large payment, then researchers should offer no payment at all.